Phase II study of a three-dose primary vaccination course of DTPa-IPV/Hib-MenC-TT followed by a 12-month Hib-MenC-TT booster in healthy infants. - Khatami, A; Snape, MD; Ohene-Kena, B; Young, K; Oeser, C; Michaelis, L; Macleod, E; Smee, H; Van Der Meeren, O; Leyssen, M; Caubet, M; Yu, L; et al. (2013)
AIM: To test for immunologic noninferiority of antibody responses to Hib and MenC using a 6-in-1 combination vaccine (DTPa-IPV/Hib-MenC-TT) compared with DTPa-IPV-Hib plus MenC-CRM197, before and after a 12-month Hib-MenC-TT booster. METHODS: Pragmatic open-label, randomized, multicenter, UK study. "6-in-1" group received DTPa-IPV/Hib-MenC-TT at 2, 3 and 4 months; control group received DTPa-IPV-Hib at 2, 3 and 4 months and MenC-CRM197 at 3 and 4 months. Both groups received Hib-MenC-TT at 12 months. Concomitant vaccines: pneumococcal conjugate vaccine at 2, 4 and 13 months, and measles, mumps and rubella vaccine at 13 months. RESULTS: One hundred forty-two children were randomized to each group. One hundred children in the "6-in-1" group and 112 control group children completed the study according-to-protocol. One month postprimary immunizations: 100% of "6-in-1" group and 93.3% of control children had anti-polyribosylribitol phosphate (PRP) IgG ≥0.15 µg/mL; 96.2% and 100%, respectively, had rSBA-MenC titers ≥1:8. One month after booster all children met these thresholds, with anti-PRP geometric mean concentrations of 66.7 (53.3; 83.5) in "6-in-1" recipients and 26.9 (20.9; 34.6) in control children (4.4 [3.5; 5.4] and 3.0 [2.2-4.2] postprimary immunizations, respectively,). rSBA-MenC geometric mean titers were 3062.9 (2421.2; 3874.6) and 954.0 (761.3; 1195.5), respectively, postbooster and 393.2 (292.5; 528.7) and 3110.5 (2612; 3704.2) postprimary. CONCLUSION: Noninferiority of DTPa-IPV/Hib-MenC-TT compared with DTPa-IPV/Hib plus MenC-CRM197 was demonstrated. In the "6-in-1" group, lower postprimary and greater postbooster rSBA-MenC geometric mean titers suggest memory B-cell priming may be favored by this vaccine over plasma cell induction. Furthermore, greater immunogenicity of TT conjugates used in both primary and booster vaccines in this group may be important.